Wiarygodność Kościoła w dzisiejszej Polsce - Kaucha, Krzysztof (Poznańskie Studia Teologiczne, 2018)
There are two purposes of this article: the first one — to clarify the meaning of the term ‘credibility of the Church in contemporary Poland’ from a theological perspective, and the second one — to describe the basic signs of such credibility and the difficulties they are facing. The article consists of three parts and a conclusion. The first part deals with the theological understanding of the Church’s credibility in contemporary Poland in the light of new researches and inspirations offered by Joseph Ratzinger’s ecclesiology and by the book Oblicza Kościoła katolickiego w Polsce. 1050. rocznicaChrztu [Features of the Catholic Church in Poland. The 1050th Anniversary of the Christening] (ed. by J. Mastej, K. Kaucha, P. Borto, Lublin 2016). The second part is focused on the signs of the Church’s credibility in Poland (sign of Peter, of the Apostolic Collegium, of unity, of holiness, of universality, of apostolicity, agapetological, praxeological, martyriological, and culture-creative), which started to be described about 25 years ago by Rev. Marian Rusecki, who was co-founder and the most excellent representative of the Lublin School of Fundamental Theology. The third part presents some new signs of the Church’s credibility in Poland according to the author of the article (charitable, staurological, resurrectional, paschal, anthropological-vocational, of freedom, of the priority of the Spirit and spiritual life, of peace and reconciliation, of protest, of the faith’s pure- ness). In the conclusion the author underlines the values of the semeiological method in describing and testing the credibility of the Church in contemporary Poland.